A Fixed Point Approach to the Stability of an Additive-Quadratic-Cubic-Quartic Type Functional Equation. (6th April 2016) - Lee, Yang-Hi; Jung, Soon-Mo
Abstract : By applying a fixed point approach, we investigate the stability problems for an AQCQ functional equation of the form f x + 2 y + f x - 2 y - 4 f x + y - 4 f x - y + 6 f x - f 2 y - f - 2 y + 4 f y + 4 f - y = 0 .